2012
DOI: 10.1016/j.neures.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of spatial frequency on reading processes for ideograms and phonograms: A high-density ERP study

Abstract: The neural substrate of the dissociation between reading Japanese ideograms (Kanji) and phonograms (Kana) is currently unclear. To test whether spatial frequency (SF) information is responsible for this phenomenon, we recorded high-density event-related potentials (ERPs) with unfiltered or spatially filtered word stimuli in Japanese-speaking subjects. Kanji (early-learned, late-learned), Kana (word, non-word), and scrambled characters served as stimuli. Fourier analysis revealed that Kanji and Kana were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 46 publications
4
30
0
1
Order By: Relevance
“…1Ab (right) and Ac (right), respectively. In a behavioral study using the same spatially filtered stimuli, no significant differences were found in their readability (subjects' mean reaction times or error rates) (Horie et al, 2012). Therefore, our spatially filtered Kanji and Kana stimuli were equally legible.…”
Section: Visual Stimulimentioning
confidence: 75%
See 4 more Smart Citations
“…1Ab (right) and Ac (right), respectively. In a behavioral study using the same spatially filtered stimuli, no significant differences were found in their readability (subjects' mean reaction times or error rates) (Horie et al, 2012). Therefore, our spatially filtered Kanji and Kana stimuli were equally legible.…”
Section: Visual Stimulimentioning
confidence: 75%
“…We found that early visual responses (P100 and N170), but not semantic processing (N400), are significantly influenced by SF, and that close links exist between Kana and LSF information and between Kanji and HSF information. Hence, we concluded that SF information contributes to the neural dissociation of Kanji and Kana reading (Horie et al, 2012). However, because the spatial resolution of ERPs is much inferior to that of functional magnetic resonance imaging (fMRI), the neural substrates involved remain unclear.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations